Eco-solution waste management potential impact on the environment, social, and economy in plastic and ceramic local industries - Abdul Aziz, Nor Azah; Bakri, Mohammed Hariri; Ghazali, Ihwan; Sufian, Atirah; Abdullah Jaafar, Johanna; Ismail, Nurul Nadia; Elloo, Mathiyalagan; Muthusamy, Elangeshwaran (Association Res Militaris, 2022)
Eco-solution waste management refers to the comprehensive management of activities that allow for the segregation of solid waste at source, the segregated transport, storage, transfer, refining, treatment and disposal of solid waste and all other activities that do not affect the environment in the management of waste. The volume of plastic waste has been increasing worldwide as plastic is one of the materials present in daily lives, since it is used as it is cheap, flexible, lightweight and durable for a number of purposes. Other than that, ceramic waste or construction waste is known to be one of the key causes of environmental and health problems, such as asbestos, which is produced and can be dangerous during demolition works. All industries should use the best alternatives way to manage all the waste properly and efficiently in order to avoid environment pollution that can harm the others. Thus, this paper aims to discuss on the current waste management practices and impact, the perception of waste recycling process or eco-solution waste management and potential impact, and to develop a recycling strategy for environment, social, and economy improvement in plastic and ceramic local industries. This case study is using a qualitative research method by doing a semi-structured interview, data transcription as well as thematic approach to find the results that are related to the research objectives. Findings shown that plastics and ceramics industries have tried their best to manage waste. The impact of these activities is positive for the environment, economy, and social of their companies even though it is not much. They have certain challenges, especially the high cost of waste recycling process. They agree with the recycling processes to improve the current waste management activities and give expectations that the impact on the environment, economy, and social will be more positive. They also agree with the proposed future recycling strategies for plastic and ceramic industry. Hence, it is possible to cycle these wastes to create other new beneficial product of green concrete as proposed by this research program. The contribution of this research is it opens ways to use waste to create other beneficial products which is green concrete for better constructions and buildings.